Impact of Irrigation Management on Salinity and Volume of Drainage Water in an 8000 ha Irrigation District in the Ebro Basin (NE Spain) - Altés, Víctor; Pascual, Miquel; Villar, Josep Maria (Spanish Journal of Soil Science, 2024)
When irrigation is introduced in a region, it adds salts and mobilizes those already present in the soil, changing the soil-plant-atmosphere continuum. These changes may lead to higher salt loads in the drainage water which, in turn, can have an impact on waters further downstream. Knowing the dynamics of these loads at the sub-basin scale is key to accounting for the possible impact that irrigation may have and to determining what improvements could be applied. This study aimed to characterise the different salt types present and to investigate drainage salt loads and their dependence upon irrigation input and their implications in irrigation management in a new, and well-managed, 8000 ha irrigation district located in the Ebro basin, NE Spain. In addition, it is relevant to highlight that the Ebro basin suffered a period of significant drought in 2023. As a result, irrigation restrictions were applied in many irrigation districts. We sought to investigate how these reductions influenced irrigation return flows and salt discharges within a selected irrigation district. The present study was undertaken during the irrigation periods of 2021, 2022, and 2023. We monitored water inputs and outputs in two representative sub-basins belonging to the Algerri-Balaguer irrigation district (Ebro basin, NE Spain). We also analysed water inputs and outputs in order to characterise and establish the salt balances in both of the sub-basins that we studied. Our results showed that during 2023, a reduction in irrigation delivery of 31% led to a reduction in drainage volume of 73%, resulting in a decrease in salt exports through drainage of 70%. These data revealed that the application of irrigation restrictions not only led to an increased availability of downstream water resources, but also to a decrease in drainage volume and salt load, resulting in an improvement in irrigation management by farmers. However, it should also be underlined that this drastic reduction in irrigation was, in turn, responsible for a reduction in yield. Re-utilising drainage waters and/or improving irrigation management at the field scale may help to find this point of balance in areas with high water demands.